2015
DOI: 10.1038/ncomms9146
|View full text |Cite
|
Sign up to set email alerts
|

Chamber identity programs drive early functional partitioning of the heart

Abstract: The vertebrate heart muscle (myocardium) develops from the first heart field (FHF) and expands by adding second heart field (SHF) cells. While both lineages exist already in teleosts, the primordial contributions of FHF and SHF to heart structure and function remain incompletely understood. Here we delineate the functional contribution of the FHF and SHF to the zebrafish heart using the cis-regulatory elements of the draculin (drl) gene. The drl reporters initially delineate the lateral plate mesoderm, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
225
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 119 publications
(244 citation statements)
references
References 49 publications
18
225
1
Order By: Relevance
“…Our data provide evidence that identifies the LPM as the lineage that gives rise to SMCs in the GI tract of zebrafish embryos by combining reporter transgene imaging and genetic lineage-tracing experiments using the LPM-expressed drl:creERT2 (Mosimann et al, 2015). Our lineage-tracing results provide the first genetic confirmation in vertebrate that smooth muscle cells in the gut region are derived from lateral mesodermal organ precursors.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Our data provide evidence that identifies the LPM as the lineage that gives rise to SMCs in the GI tract of zebrafish embryos by combining reporter transgene imaging and genetic lineage-tracing experiments using the LPM-expressed drl:creERT2 (Mosimann et al, 2015). Our lineage-tracing results provide the first genetic confirmation in vertebrate that smooth muscle cells in the gut region are derived from lateral mesodermal organ precursors.…”
Section: Discussionsupporting
confidence: 63%
“…The LPM is patterned early into distinct regions that will give rise to precursors of kidney, heart, endothelium, hematopoietic and limb cell fates (Davidson and Zon, 2004;Gering et al, 2003;Mosimann et al, 2015). Although previous work has suggested that iSMCs arise from the lateral plate mesoderm (LPM), genetic demonstration for this origin is still missing in a vertebrate model (Roberts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We injected the sgRNA complexed with Cas9 protein as solubilized RNPs [11] at sub-optimal concentration to achieve viable mosaicism (see Methods for details) in the multicolor Tg(lmo2:dsRED2;drl:EGFP;myl7:mCyan) reporter background, subsequently abbreviated as RGB. In RGB embryos, dsRED2 labels endothelial, hematopoietic, and endocardial progenitors (lmo2) in red [14], EGFP marks all lateral plate mesoderm lineages (drl) including pectoral fins in green [15], and AmCyan reveals the differentiated cardiomyocytes (myl7 ) in blue [16]; consequently, RGB enables in vivo imaging of all cardiovascular and additional LPM lineages over the first 3 days of development. From F0 outcrosses that transmitted mutant tbx5a alleles, we genotyped adult F1 zebrafish for the presence of mutated tbx5a alleles by tail clipping, PCR, sequencing, and CrispRVariants analysis [17].…”
Section: Resultsmentioning
confidence: 99%